Analysis on the status quo and influencing factors of work engagement of neurology nurses (神经科护士工作投入的现状及影响因素分析) - FU Jing (富晶); Li Jing (苏娅丽); SU Yali (夏小童); ZHAO Rui (赵彬彬); ZHAO Binbin (许继飞); MA Shengwei (刘宇) (中西医结合护理)
Objective To analyze the current situation and influencing factors of work engagement of neurology nurses. Methods Using the convenient sampling method, a cross-sectional survey was conducted among nurses in the department of neurology in a Class III and Class A general hospital in Beijing from April to May 2022. The self-designed general data questionnaire, the work engagement scale and the Chinese version of the perceived stress scale were used to survey the nurses in the department of neurology. Results In this study, a total of 660 questionnaires were distributed and 630 were recovered, with a recovery rate of 95. 45%. Totally 630 questionnaires were valid, with an effective rate of 100. 00%. Of the 630 neurology nurses, 34 were male (5. 40%) and 596 were female (94. 60%). The score of work engagement of 630 neurology nurses was (35. 15 ± 5. 34), and the data difference was statistically significant (P＜0. 05). The results of univariate analysis showed that there were statistically significant differences in the scores of work engagement of neurology nurses in terms of age, employment relationship, technical title, working years and children's situation (P＜0. 05). The total score of perceived stress of neurology nurses was (36. 76 ± 8. 10), and the total score of work engagement was positively correlated with the score of sense of loss and perceived stress (P＜0. 05), and negatively correlated with the score of tension (P＜0. 05). The results of multifactor analysis showed that the sense of loss of control, employment relationship, and working for 1～10 years were the independent influencing factors of work engagement (P＜0. 05). Conclusion There are several factors affecting the work engagement of neurology nurses. As clinical nursing managers, they can adopt effective scientific management methods and take effective measures to relieve the psychological pressure of nurses, reduce the level of rumination thinking, and positively guide the establishment of positive emergency psychology, so as to improve the degree of nurses' work engagement, and ultimately achieve the goal of improving nursing quality and patient satisfaction. (目的 分析神经科护士工作投入现状及其影响因素。方法 采用便利抽样的方法, 于2022年4月—5月对北京某三级甲等综合医院神经科护士进行横断面调查。采用自行设计的一般资料调查问卷、工作投入量表、中文版知觉压力量表, 对神经科护士进行调查问卷。结果 本研究共发放问卷660份, 回收630份, 回收率95. 45%; 有效问卷630份, 有效率100. 00%。630名神经科护士工作投入得分为(35. 15±5. 34)分, 各个维度的平均分对比, 差异有统计学意义(P<0. 05)。单因素分析结果显示, 神经科护士的工作投入评分在年龄、聘用关系、技术职称、工作年限和子女情况上的差异有统计学意义(P＜0. 05)。神经科护士的知觉压力总分为(36. 76±8. 10)分, 工作投入总分与失控感评分、知觉压力总分呈正相关(P＜0. 05), 与紧张感评分呈负相关(P＜0. 05)。多因素分析结果显示, 失控感、聘用关系、工作1～10年、紧张感是工作投入的独立影响因素(P＜0. 05)。结论 神经科护士工作投入的影响因素众多。作为临床护理管理者可以通过有效的科学管理办法, 采取有效措施缓解护士心理压力, 降低反刍思维水平, 正向引导建立正向的应急心理, 从而提高护士工作投入程度, 最终达到提高护理质量和患者满意度的目的。)